Determination of the optimum conditions in the removal of Bomaplex Red CR-L dye from the textile wastewater using O3, H2O2, HCO3- and PAC - Oguz, E; Keskinler, B; Çelik, C; Çelik, Z (Elsevier, 2006)
Bomaplex Red CR-L textile dye was used in the experimental studies. Taguchi method was applied to determine optimum conditions in the removal of dye from synthetic textile wastewater. After the parameters were determined to remove Bomaplex Red CR-L dye from synthetic textile wastewater, the experimental studies were realized. The chosen experimental parameters and their ranges: HCO3- (mM), 0-39; temperature (degrees C), 18-70; ozone-air flow rate (1min(-1)), 5-15; the dye concentration (ppm), 200-600; particulate activated carbon (PAC) (g), 0-1.5; H2O2 (MM), 0-0056; pH, 3-12; and treatment time (min), 10-30, respectively. An orthogonal array L-18 (2(1) x 3 7) for experimental plan and the smaller the better performance statistics formula were selected to define optimum conditions. The optimum conditions were found to be as follows: HCO3-(mM), 0; temperature (degrees C), 70; ozone-air flow rate (1 min(-1)), 10; the dye concentration (ppm), 200; particulate activated carbon (PAC) (g), 1; H2O2,(mM), 0.056; pH, 12; and time (min), 20. Under these optimum conditions, it was determined that the Bomaplex Red CR-L removal efficiency from textile wastewater was 99%. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ozonatiom; Bornaplex Red CR-L dye; PAC; H2O2; Taguchi method